Downsizing of Electric Motors by Utilizing Differential Gear for Traction and Hydraulic Pump of Heavy Mobile Machine - Topias Tyni; Jari Vepsalainen (IEEE Access)
Heavy mobile machines should be productive and energy efficient. Electrification drives and enables the design of new solutions that can outperform older technologies. While components of heavy mobile machines should be as small, inexpensive, and reliable as possible, all components should also be utilized extensively to maximize space usage. This is achieved through proper sizing and multifunctional use of components. In this paper, a novel utilization of a differential gear mechanism is proposed to couple two electric motors and a hydraulic pump. The analysis focuses on the simultaneous operation of a traction drive and working hydraulics in a wheel loader application. Simulations utilizing a recorded driving cycle are used to analyze the torque distribution of the electric motors. The performance of the coupling system is compared to a reference system where the electric motors are separated and working independently. The results indicate that the differential dual-motor system can easily reduce the torque demand of the traction motor by 20 percent in an uphill section, and also significantly reduce the torque demand during simultaneous operation compared to the reference system. However, the energy efficiency of the proposed system decreased by 4 percent in simultaneous operation compared to the reference system.